Heat-killed Lactobacillus acidophilus suppresses SARS-CoV-2 infection in the human intestinal epithelial cell line Caco-2 - Takada, Kazuhide; Trinh, Quang Duy; Takeda, Yoshinori; Tsuji, Noriko M.; Hayakawa, Satoshi; Komine-Aizawa, Shihoko (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe gastrointestinal (GI) tract is suspected to be a possible source for the systemic spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as well as a reservoir of long coronavirus disease (COVID). Thus, the mucosal epithelial tissue of the colon is a potential target for probiotics to help control SARS-CoV-2 infection. Recently, the effect of live probiotics on COVID-19 has been evaluated. However, live probiotics have certain risks, including the transmission of antibiotic-resistant genes, disturbance of gut colonization in infants, and systemic infections induced by translocation. Therefore, there is growing interest in nonviable microorganisms, particularly heat-killed probiotic bacteria, to mitigate these risks.MethodsThis study evaluated the antiviral properties of heat-killed Lactobacillus acidophilus (HK-LA) in the Caco-2 cell line. Caco-2 cells were infected by SARS-CoV-2 with or without 24-hour pretreatment of HK-LA and the presence of HK-LA during infection.ResultsRT-qPCR analysis showed that HK-LA treatment significantly reduced SARS-CoV-2 genome copies by approximately 30%. Similarly, flow cytometry revealed a roughly 30% decrease in SARS-CoV-2 spike-positive Caco-2 cells following HK-LA treatment. Additionally, ELISA demonstrated a significant increase in IFN-λ2 secretion induced by HK-LA.DiscussionHK-LA reduces viral infection in Caco-2 cells with an increase in IFN-λ2 secretion. Therefore, heat-killed lactobacilli could potentially reduce SARS-CoV-2 infection in the GI tract, suggesting a possible clinical application.